Vloga in pomen znanja v teoriji rasti - Kešeljević, Aleksandar (Naše gospodarstvo, 2006)
The paper focuses on knowledge, which is becoming one of the most important factors in achieving a competitive advantage. The connection between knowledge on one hand, and information, human capital, factors of production and technological progress on the other, is well understood in economic theory. The goal of the paper is to present different periods in growth theory in order to be able to show that knowledge has become one of the key issues in growth theory. The author points out that growth theory will not be able to prosper and develop in the future without a sound and coherent definition of knowledge as a productive factor.
Keywords: podjetja; konkurenčnost; razvojna strategija; rast; razvoj podjetja; intelektualni kapital; knowledge; znanje; informacije; tehnološki razvoj; ekonomske teorije